1996
DOI: 10.1021/bi951659y
|View full text |Cite
|
Sign up to set email alerts
|

113Cd Nuclear Magnetic Resonance Studies of Cabbage Histidinol Dehydrogenase

Abstract: Histidinol dehydrogenase (HDH), a dimeric protein, catalyzes two sequential oxidation reactions to yield L-histidine from L-histidinol via L-histidinal. HDH contains 1 mol of Zn(II) per mol of subunit, and removal of this metal abolishes the enzymatic activity. On substitution of Zn(II) with 113Cd(II), the enzyme ([113Cd]HDH) showed similar catalytic activity. The 113Cd NMR spectra of [113Cd]HDH were measured under various conditions. The 113Cd NMR spectrum of [113Cd]HDH showed a resonance at 110 ppm, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…The presence of His-262 and His-419 in the Zn 2ϩ coordination environment is consistent with previous mutagenesis experiments (15). NMR experiments (16) suggested that the amino group of the ligand (including L-histidinol, histamine, and L-histidine) is not involved in Zn . The best-defined electron density corresponds to the phosphate groups and to the adenosine moiety, whereas the density for the nicotinamide is poorly defined (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of His-262 and His-419 in the Zn 2ϩ coordination environment is consistent with previous mutagenesis experiments (15). NMR experiments (16) suggested that the amino group of the ligand (including L-histidinol, histamine, and L-histidine) is not involved in Zn . The best-defined electron density corresponds to the phosphate groups and to the adenosine moiety, whereas the density for the nicotinamide is poorly defined (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The Zn 2ϩ ion is essential for enzymatic activity, although other metals such as Mn in forming an active enzyme (13). Biochemical and mutagenesis studies on HisD from S. typhimurium (12,14) and Brassica oleracea (15) have identified two histidine residues, corresponding to His-262 and His-419 from E. coli, as part of the active site, although the precise role of His-262 has not been established (14)(15)(16). NMR measurements indicated that the substrate participates in Zn 2ϩ coordination through its imidazole ND1 and alcohol oxygen atoms (16), and Zn 2ϩ has been proposed to participate directly in catalysis (14,16).…”
mentioning
confidence: 99%
“…Hereafter, for convenience, the corresponding metal binding sites at 110, 83, 22, and −2 ppm will be represented as A, A′, A″, and B, respectively. Thus, in the presence of excess Cd 2+ , Cd 2+ ions at site A readily exchange with free Cd 2+ ions faster than those for sites A′ and A″ although, in the absence of excess 113 Cd 2+ ion, extensive dialysis by Tris‐SO 4 buffer cannot remove 113 Cd 2+ ion from [ 113 Cd]HDH [3]. This fact also suggests that the environmental change around site A (peak at 110 ppm in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…113 Cd metal (95 atom %) was obtained from ISOTEC Inc. (Miamisburg, OH). [ 113 Cd]SO 4 was prepared as described previously [3]. NAD + and l ‐histidinol were purchased from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation